How Can Artificial Intelligence Empower Teacher Development: Connotation and Cultivationof Teachers'Artificial Intelligence Literacy - HU Wei (Jiaoshi jiaoyu xuebao, 2024)
The development of new technologies such as artificial intelligence has promoted the digital transformation of education around the world. ChatGPT, as a representative of generative artificial intelligence, poses new challenges to the field of education and also puts forward new requirements for teacher quality. Artificial intelligence literacy is the core qualitythat teachers need to adapt to the era of AI. Based on the analysis of the connotation of quality, teacher qualityand artificial intelligence literacy, teacher artificial intelligence literacy refers to the qualitythat teachers, as human-machine collaborative teachers, need to understand and use artificial intelligence educational application products in the context of the artificial intelligence era. In the AI era, teachers'artificial intelligence literacy includes three primary elements: AI knowledge, AI skills, and AI attitude and ethics, as well as fifteen secondary elements like knowledge of AI fact, knowledge of AI principle, skills of identifying AI, skills of analyzing AI, guarantee of student safety, and protection of student privacy, etc.It is effective tocultivate teachers' artificial intelligence literacy from three levels: government, school and teachers themselves.